Pengaruh Pemberian Minuman Jahe Terhadap Penurunan Hiperemesis Gravidarum Pada Ibu Hamil Trimester 1 di Klinik Pratama Keluarga Sehat - Dwi Rosmawati (Pelantar Press, 2024)
Hyperemesis gravidarum is excessive nausea and vomiting in pregnant women that can interfere with maternal and fetal health. Ginger has long been used as a traditional medicine to treat nausea and vomiting. This study aims to determine the effect of giving ginger drink on reducing hyperemesis gravidarum in first trimester pregnant women.This research plan uses experimental method (pre-experiment), with one group pretest posttes design. The population in this study were 11 first trimester pregnant women who experienced hyperemesis gravidarum at the Keluarga Sehat Private Clinic. Data were collected using a questionnaire to measure the frequency of nausea and vomiting and observation to measure the severity of hyperemesis gravidarum. The results showed that from the data analysis using the t-test, it was found that t count more than t table, namely 4.183 more than 2.228 and based on significance, it was found that the significance value was less than 0.05, namely 0.02, so ho was rejected and ha was accepted, meaning that there was an influence between the implementation of ginger drink in reducing hyperemesis gravidarum in 1st trimester pregnant women. There is a decrease in hyperemesis gravidaraum after being given ginger drinks, there is an effect of giving ginger drinks on reducing hyperemesis gravidarum in pregnant women in the first trimester at the Keluarga Sehat Private Clinic. (p value equal 0.00).